P641 Implementation and short-term adverse events of anti-SARS-CoV-2 vaccines in Inflammatory Bowel Disease patients: an international web-based survey. (21st January 2022) - Revés, J; Abreu, B; Chaparro, M; Gisbert, J P; Mariangela, A; Fiorino, G; Barberio, B; Zingone, F; Pisani, A; Cassar, D; Michalopoulos, G; Mantzaris, G; et al.
Abstract: Background: Pivotal anti-SARS-CoV-2 vaccines clinical trials did not include patients with immune-mediated conditions such as inflammatory bowel disease (IBD). We aimed to describe the implementation of anti-SARS-CoV-2 vaccines among IBD patients, patients' concerns before vaccination and side-effect profile of the anti-SARS-CoV-2 vaccines using real-world data. Methods: An anonymous web-based self-completed survey was distributed in 36 European countries between June and July 2021. The results of patients' characteristics, concerns, vaccination status and side-effect profile were analysed using descriptive statistics and logistic regression. Results: Among the 3272 IBD patients completing the survey (0.1% of the IBD European population), 79.6% had received at least one dose of the anti-SARS-CoV-2 vaccine, and 71.7% had completed the vaccination process. Most of the patients (70.6%) were vaccinated with the Pfizer-BioNTech (BNT162b2) vaccine. Patients over 60 years old had a significantly higher rate of vaccination (OR 2.98, 95% CI 2.20–4.03, p<0.001). Patients' main concerns before vaccination were the possibility of having worse vaccine-related adverse events due to their IBD (24.6%), having an IBD flare after vaccination (21.1%) and reduced vaccine efficacy due to IBD or associated immunosuppression (17.6%). After the first dose of the vaccine, 72.4% had local symptoms at the injection site and 51.4% had systemic symptoms (5 patients had non-specified thrombosis). Adverse events were less frequent after the second dose of the vaccine and in older patients. When comparing with previous studies from the general population, the IBD patients answering the survey did not seem to have increased side effects (Table 1). Only a minority of the patients were hospitalized (0.3%), needed a consultation (3.6%) or had to change IBD therapy (13.4%) after anti-SARS-CoV-2 vaccination. Conclusion: Although IBD patients raised concerns about the safety and efficacy of anti-SARS-CoV-2 vaccines, the implementation of vaccination in those responding to our survey was high and the adverse events were comparable to the general population, with minimal impact on their IBD.